2010
DOI: 10.22201/fesi.20071523e.2010.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction in interaction with self-esteem, peer influence and dietary restraint: A systematic review / Insatisfacción corporal en interacción con autoestima, influencia de pares y dieta restrictiva: Una revisión

Abstract: Abstract. Several researches have been realized in order to understand the role of body dissatisfaction in the development of Eating Disorders (ED). Despite this, there are few reviews that permit have insight in what has been found and where future research should be addressed. So, the aim of this paper was to make a systematic review of those articles in which was evaluated body dissatisfaction in interactions with biopsychosocial factors. For this was done a search in the databases MEDLINE, PsycINFO and Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
0
4
0
4
Order By: Relevance
“…However, we must be cautious when interpreting the results, as there is no clear balance between the sample number of females and males participating in such studies (the volume of the female population studied was significantly greater than the male population). One possible reason for this could be that throughout history, females have always been considered as most vulnerable and most at risk of developing eating disorders (Amaya et al, 2010; Laus et al, 2014). Studies that did take into account the limitations of the samples — an unbalanced proportion of females and males — found that the male population also feels dissatisfied with their body image, manifesting, as females do, a greater desire to lose weight or stay slim, along with a desire to increase their muscle mass.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we must be cautious when interpreting the results, as there is no clear balance between the sample number of females and males participating in such studies (the volume of the female population studied was significantly greater than the male population). One possible reason for this could be that throughout history, females have always been considered as most vulnerable and most at risk of developing eating disorders (Amaya et al, 2010; Laus et al, 2014). Studies that did take into account the limitations of the samples — an unbalanced proportion of females and males — found that the male population also feels dissatisfied with their body image, manifesting, as females do, a greater desire to lose weight or stay slim, along with a desire to increase their muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…En cuya formación intervienen, con distinto peso, factores de carácter: individual, social y cultural. Entre los cuales, cobran especial relevancia ‘los modelos estéticos corporales’ (Amaya, Álvarez, & Mancilla, 2010; Bully, Elosua, & López-Jáuregui, 2012).…”
Section: Diferencias De Género Existentes En La Población General En ...unclassified
See 3 more Smart Citations